The Effects of organizational change on students’ emotions - Rahmawati, Nada; Wok, Saodah (GATR Enterprise, 2017)
Organizational change can produce a number of positive and negative emotional responses. This study uses the Theory of Emotional Contagion (Hatfield, Cacioppo & Rapson, 1993) where negative as well as positive feelings can be transferred to others. The aims of the study are to examine the effects of perception on technological change, leadership change and structural change towards students’ emotions; and to analyze the mediating effect of experience on perception and emotion resulting from organizational changes. The study employs the quantitative research design using the survey method with the self-administered questionnaire. A total of 223 respondents was collected from among the undergraduate students at a faculty in a public university who have faced organizational changes (technological, leadership and structural). Results reveal that perceptions of technology, leadership and structural changes are found to have moderate effects on students’ emotions. However, experiences of change partially mediate students’ emotion and perception of technological, leadership and structural changes. Experience with organizational changes affect students’ emotions badly. This implies that the Emotional Contagion Theory holds true for organizational changes as the hypotheses are supported.